The Influence of Electrode Shape on the Electric and Temperature Fields in an Immersed High-Voltage Electrode Boiler - Mingyong Wang; Jianfei Wang; Yiling Zhang; Lu Li; Wenkai Zhou; Zhipeng Lei (Energies)
The electric and temperature fields formed in the furnace water system by electrodes of different shapes differ to some extent when the immersed high-voltage electrode boiler is in operation. To obtain the distribution of electric and temperature fields in the furnace water when different shapes of electrodes are used in a high-voltage electrode boiler, simulation models of spherical electrodes, planar electrodes, and tangential electrodes are established, respectively. The effects of the electrode structure on the electric and temperature fields in the furnace water were investigated. The simulation results show that the electric field distribution and temperature field distribution of the spherical electrode in the furnace water are the best among the three electrode structures. Meanwhile, in order to verify the accuracy of the adopted simulation method, simulation and temperature rise tests were carried out on a small spherical electrode model under 400 V AC, and the simulation calculation results and the temperature rise test results at special points were compared. The difference between the simulation and test results is less than 3%, which proves the reasonableness of the method. The method can be used as a reference for the design of electrodes for immersed high-voltage electrode boilers, as well as the analysis of electric and temperature fields around the electrodes.